Impact of ground plane scattering on performance of reconfigurable intelligent surface - Murata, Kentaro; Lau, Buon Kiong; Honma, Naoki (IEEE International Symposium on Antennas and Propagation and USNC-URSI Radio Science Meeting, USNC-URSI 2023, Portland, Oregon, United States, 2023-07-23 - 2023-07-28, 2023)
Reconfigurable intelligent surfaces (RISs) are being considered for 6G as they can facilitate favourable radio channels. To rigorously model the characteristics of an array antenna-based RIS, this paper proposes an approach to separately evaluate scatterings from the antenna elements and ground plane of RIS. Simulation results show that, depending on the absolute phases of variable loads in the RIS, the scattering from the ground plane can have a non-negligible effect on the performance of the RIS.
Keywords: scattering; Reconfigurable intelligent surface (RIS); 6G